Implementation of value-based healthcare in ophthalmology: a scoping review - Moh Anfasa Giffari Makkaraka; Zulkarnain Abubakar; Amal Chalik Sjaaf; Tjahjono Darminto Gondhowiardjo (BMJ Open Ophthalmology)
Objective This review aimed to identify and summarise how value-based healthcare (VBHC) is implemented in the field of ophthalmology.Methods A scoping review was conducted by searching empirical and non-empirical articles from from electronic databases (PubMed, Science Direct, ProQuest and Scopus) and other methods starting January 2006 (the year Porter and Teisberg introduced VBHC) up to 31 December 2023.Results 1.081 records were screened, and 12 articles (8 empirical studies and 4 non-empirical articles) were used for data extraction. Most articles were published in the UK. Most articles described the implementation of VBHC agenda by measuring outcomes and costs. All the included empirical studies reported implementation effect; otherwise, non-empirical articles were only described proposed implementation.Conclusion The implementation of VBHC in ophthalmology has shown a positive impact on enhancing patient value and reducing healthcare costs. Nevertheless, the study highlighted that no provider or healthcare system has fully embraced and implemented VBHC, comprehensively addressing the entire value agenda.